Haemoglobin S and C affect the motion of Maurer's clefts in Plasmodium falciparum-infected erythrocytes - Kilian, Nicole; Dittmer, Martin; Cyrklaff, Marek; Frischknecht, Friedrich; Sanchez, Cecilia P.; Lanzer, Michael (Cellular microbiology, 2013)
The haemoglobinopathies S and C protect carriers from severe Plasmodium falciparum malaria. We have recently shown that haemoglobin S and C interfere with host-actin remodelling in parasitized erythrocytes and the generation of an actin network that seems to be required for vesicular protein trafficking from the Maurer's clefts (a parasite-derived intermediary protein secretory organelle) to the erythrocyte surface. Here we show that the actin network exerts skeletal functions by anchoring the Maurer's clefts within the erythrocyte cytoplasm. Using a customized tracking tool to investigate the motion of single Maurer's clefts, we found that a functional actin network restrains Brownian motion of this organelle. Maurer's clefts moved significantly faster in wild-type erythrocytes treated with the actin depolymerizing agent cytochalasin D and in erythrocytes containing the haemoglobin variants S and C. Our data support the model of an impaired actin network being an underpinning cause of cellular malfunctioning in parasitized erythrocytes containing haemoglobin S or C, and, possibly, for the protective role of these haemoglobin variants against severe malaria.